Ethical Expression of Cleanliness as Part of Faith A Hadith and Green-Sufism Perspective - aisah, Siti (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This research examines the concept of Green-Sufism as a holistic approach to preserve the environment based on the ethical expression â€œCleanliness as a Part of Faith''. Green-Sufism teaches that nature is not merely an object to be exploited, but it also as the part of a living entity which has value and meaning. This concept emphasizes physical, moral, social, and spiritual cleanliness as the foundation of environmental conservation actions. Research method that is conducted on this topic is descriptive-qualitative, based on the signifier analysis of the meaning of cleanliness (faith) and literature study to support and strengthen the concept of Green-Sufism. The result of this research found thatÂ â€œcleanliness as a part of faithâ€ encompasses physical, moral, social, and spiritual cleanliness. Mahabbah (love), Uzlah (self-isolation), and Zuhud (asceticism) practices become implementation parts of cleanliness in the Green-Sufism perspective. These practices serve as motivational achievements of Makrifat, representing the perfection of Sufi thought in preserving the environment as forms of devotion and worship for God. Through these understandings, humans should achieve balance and harmony in their relationship with the environment and maintain environmental sustainability for common prosperity.